Application of benchtop humidity and temperature chamber in the measurement of water vapor sorption in US shales from Mancos, Marcellus, Eagle Ford and Wolfcamp formations - Abdulelah, H. (Springer Science and Business Media Deutschland GmbH, 2022)
A benchtop humidity and temperature chamber was used to assess water vapor sorption in four US shale samples at 90Â Â°C. Water sorption isotherms were measured at relative humidity ranging from 10 to 99 and temperature of 90Â Â°C. Shale fractal properties were then evaluated, and capillary pressure (ranging from 1.70 to 386Â MPa) was obtained using Kelvin relationship. The results show that Mancos shale, from the US, adsorbed more absorbed water due to its high clay concentration and low TOC. However, Wolfcamp shale, from the US, has the lowest TOC and clay concentration, adsorbing the lowest amount of water. There is little hysteresis between adsorption and desorption isotherms explaining water retention phenomenon in some shales. The obtained fractal dimension values ranged between 2.45 and 2.76 and average of 2.56 indicating irregular pore surface and complex pore structure. All shale sample's capillary curves were fitted to Brooks & Corey and van Genuchten models with nonlinear regression. The fitting coefficient, R2, which represents the proportion of variance for Brooks & Corey fits ranged from 0.90 to 0.97 for imbibition and 0.85 to 0.98 for drainage, while R2 for the van Genuchten model ranged from 0.94 to 0.99 for both imbibition and drainage. Thus, the proposed method can be used to measure capillary pressureâsaturation relationships in gas shales. Â© 2022, The Author(s).